Eplerenone, diabetes, and chronic kidney disease in patients hospitalized for acute heart failure: findings from the EARLIER trial - Masatake Kobayashi; Akira Yamashina; Kazuhiro Satomi; Masataka Watanabe; Ryu Takagi; Ayako Tezuka; Shin Ito; Masanori Asakura; Masafumi Kitakaze (Cardiovascular Diabetology, 2025)
Abstract Background Mineralocorticoid receptor antagonists (MRAs) are often underutilized in patients with heart failure (HF), particularly those with diabetes and/or chronic kidney disease (CKD). However, the impact of concurrent diabetes and CKD on the efficacy and safety of eplerenone in acute HF remains uncertain. Methods The EARLIER trial enrolled patients with acute HF, who were randomized to receive eplerenone or placebo for 6 months. Patients were categorized based on the presence of diabetes and/or CKD (defined by eGFR < 45 ml/min/1.73 m2 or UACR ≥ 30 mg/g), and the associations between diabetes/CKD categories and cardiovascular outcomes were assessed. The effects of eplerenone on HF-related outcomes (i.e., cardiovascular death, HF hospitalization, worsening HF, or out-of-hospital diuretic intensification) and adverse events were also assessed across diabetes/CKD status. Results Among 300 patients (mean age 67 ± 13 years; 73% male), 39% had diabetes, mean estimated glomerular filtration rate was 63 ± 18 ml/min/1.73 m2, median urine albumin-to-creatinine ratio was 34 mg/g (13–84 mg/g), and 58% had CKD. Patients with both diabetes and CKD (26%) had a higher risk of cardiovascular death and/or hospitalization compared to those without either disease (HR, 95% CI = 2.57, 1.29–5.12; P = 0.007, P-for-interaction = 0.049), and poor prognosis persisted after adjusting for covariates (i.e., natriuretic peptide) (adjusted-HR, 95% CI = 2.33, 1.12–4.84; P = 0.02). Furthermore, the effects of eplerenone on HF-related outcomes and adverse events were consistent regardless of diabetes/CKD categories (all-P-for interaction > 0.05). Conclusions In patients with acute HF, the combination of diabetes and CKD was associated with an increased risk of cardiovascular events. However, the efficacy and safety of eplerenone were not influenced by diabetes and CKD status. Graphical abstract